PENGUKURAN KUALITAS SUMBER DAYA MANUSIA MELALUI INDEKS PEMBANGUNAN MANUSIA DAN INDEKS MUTU HIDUP SERTA PENGARUHNYA TERHADAP PRODUKTIVITAS TENAGA KERJA DI PROVINSI JAMBI - Azizah Azizah (Universitas Batanghari Jambi, 2013)
Quality of human resources is inseparable from the work productivity of the human resources , since the quality of human resources can be seen from his productivity . Quality of human resources as well as the subject of development can determine the level of productivity will also determine the success of development and productivity is the driving force for economic development . So it can be said that the improvement of the quality of human resources is reflected in the contribution to economic growth is getting better . Factors affecting the quality of the society at large is the factor income , educational factors and health factors . Improvement of health , education and income levels give you an idea on improving the quality significantly.Based on estimates using the OLS method , showing the influence of the human development index (HDI) and the Quality of Life Index ( IMH ) on labor productivity Jambi province has a positive and significant effect can be seen from the calculated value of t is greater than t - table .Keywords: The Quality of Life Index (IMH), The Human Development Index, and Labor Productivity